2011
DOI: 10.1183/09031936.00037711
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency in pulmonary arterial hypertension: a potential therapeutic target

Abstract: Iron deficiency is known to be common and detrimental in chronic left heart failure, where parenteral iron treatment has been shown to improve exercise capacity, New York Heart Association functional class and patient wellbeing. There is now increasing interest in the role of iron in the natural history of pulmonary arterial hypertension (PAH). Iron availability influences the pulmonary vasoconstrictor response to hypoxia and accumulating evidence indicates that iron deficiency is prevalent in idiopathic and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
76
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 87 publications
4
76
0
2
Order By: Relevance
“…This interaction between iron, hypoxia and the pulmonary circulation is consistent with known effects of iron on the hypoxiainducible factor (HIF) family of transcription factors and involvement of HIF in regulating cardiopulmonary physiology [2][3][4]. Studies from several centres have subsequently confirmed a link between iron status and idiopathic pulmonary arterial hypertension, demonstrating that iron deficiency is unexpectedly common in this disease and independently worsens morbidity and mortality (recently reviewed by Rhodes et al [5]). Two European studies investigating the use of intravenous iron in pulmonary arterial hypertension are now underway [5].…”
supporting
confidence: 76%
See 2 more Smart Citations
“…This interaction between iron, hypoxia and the pulmonary circulation is consistent with known effects of iron on the hypoxiainducible factor (HIF) family of transcription factors and involvement of HIF in regulating cardiopulmonary physiology [2][3][4]. Studies from several centres have subsequently confirmed a link between iron status and idiopathic pulmonary arterial hypertension, demonstrating that iron deficiency is unexpectedly common in this disease and independently worsens morbidity and mortality (recently reviewed by Rhodes et al [5]). Two European studies investigating the use of intravenous iron in pulmonary arterial hypertension are now underway [5].…”
supporting
confidence: 76%
“…Studies from several centres have subsequently confirmed a link between iron status and idiopathic pulmonary arterial hypertension, demonstrating that iron deficiency is unexpectedly common in this disease and independently worsens morbidity and mortality (recently reviewed by Rhodes et al [5]). Two European studies investigating the use of intravenous iron in pulmonary arterial hypertension are now underway [5].…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…12 Second, use of the Ganzoni formula may not be reliable in iPAH patients with hypoxemia-driven erythropoiesis and consequent hemoglobin (Hb) levels within the normal range despite iron deficiency. 11,13 Third, previous studies with iron therapy showed that the mean dose of iron needed was around 1,000 mg or even higher. 10 One of the concerns was that patients might increase their Hb levels above reference values, which could be detrimental since this increases blood viscosity.…”
Section: Intravenous Iron Safely Increased Body Iron Stores and Qualimentioning
confidence: 99%
“…The effect of selexipag exposure on erythrocytes and hemoglobin was investigated since PAH patients frequently encounter anemia 8. Vital signs (blood pressure, heart rate), occurrence of prostacyclin‐related and hemorrhage AEs were investigated since prostacyclin analogs are known to have vasodilatory and platelet aggregation inhibitory effects.…”
Section: Methodsmentioning
confidence: 99%